2019
DOI: 10.3389/fimmu.2019.02081
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica Infection in Cattle: Analyzing Responses of Peripheral Blood Mononuclear Cells (PBMC) Using a Transcriptomics Approach

Abstract: The parasitic helminth Fasciola hepatica (liver fluke) causes economic loss to the livestock industry globally and also causes zoonotic disease. New control strategies such as vaccines are urgently needed, due to the rise of drug resistance in parasite populations. Vaccine development requires a comprehensive understanding of the immunological events during infection. Previous in vivo studies by our group have investigated global differentially expressed genes (DEGs) in ovine peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 69 publications
6
42
3
Order By: Relevance
“…This cell subset is not MHC restricted and can recognise peptides via a mechanism that requires direct cell-cell contact with an antigen presenting cell and signalling through the γδTC [45][46][47]. In addition, it was recently reported in two transcriptomic studies conducted in cattle and sheep infected with F. hepatica that major differences exist in the expressed genes related to immune response, and that the proportion of differentially expressed genes (DEGs) observed between acute and chronic stages of the infection was responsible for up to more than 70% of the total DEGs at the acute stage in sheep, whereas this percentage decreased to about 5% in cattle [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…This cell subset is not MHC restricted and can recognise peptides via a mechanism that requires direct cell-cell contact with an antigen presenting cell and signalling through the γδTC [45][46][47]. In addition, it was recently reported in two transcriptomic studies conducted in cattle and sheep infected with F. hepatica that major differences exist in the expressed genes related to immune response, and that the proportion of differentially expressed genes (DEGs) observed between acute and chronic stages of the infection was responsible for up to more than 70% of the total DEGs at the acute stage in sheep, whereas this percentage decreased to about 5% in cattle [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, -omics studies aimed at investigating the changes in host tissues upon contact with FhNEJ are even more scarce than those focused on immature parasites. A few in vivo studies after F. hepatica infection have addressed transcriptomic analyses of peripheral blood mononuclear cells from sheep [92][93][94] and liver cells collected from sheep [95] and mice [96]. A novel proteomic analysis of the peritoneal fluid from infected sheep has also been recently published [97].…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%
“…On the other hand, differences in the immune response to infection may account for differences in host susceptibility. In the initial stages of infection there is a mixed systemic response with activation of T h 1/T h 2/Treg pathways, while in chronic infection the immune response shifts towards T h 2 activation, with sheep usually showing this pattern earlier than cattle (6)(7)(8). It has been shown that this shift is at least partly induced by molecules released by the parasite.…”
Section: Introductionmentioning
confidence: 99%